1) Полагаю, что n ∈ Z
5, \ 0! = 1, \ n! = 1*2*...*n\\\\ (n-1)*(n-2)*(n-3)*(n-4)*(n-5) =\\ (n-1)!/(n-6)!\\\\ (1-n)*(n-2)*(n-3)*(n-4)*(n-5) =\\ -(n-1)*(n-2)*(n-3)*(n-4)*(n-5) =\\-(n-1)!/(n-6)!\\\\ (n-1)*(2-n)*(n-3)*(n-4)*(n-5) =\\ -(n-1)*(n-2)*(n-3)*(n-4)*(n-5) =\\ -(n-1)!/(n-6)!\\\\ (1-n)*(2-n)*(3-n)*(4-n)*(5-n) =\\ (-1)^5(n-1)*(n-2)*(n-3)*(n-4)*(n-5) =\\ -(n-1)!/(n-6)!\\\\" alt="if \ n > 5, \ 0! = 1, \ n! = 1*2*...*n\\\\ (n-1)*(n-2)*(n-3)*(n-4)*(n-5) =\\ (n-1)!/(n-6)!\\\\ (1-n)*(n-2)*(n-3)*(n-4)*(n-5) =\\ -(n-1)*(n-2)*(n-3)*(n-4)*(n-5) =\\-(n-1)!/(n-6)!\\\\ (n-1)*(2-n)*(n-3)*(n-4)*(n-5) =\\ -(n-1)*(n-2)*(n-3)*(n-4)*(n-5) =\\ -(n-1)!/(n-6)!\\\\ (1-n)*(2-n)*(3-n)*(4-n)*(5-n) =\\ (-1)^5(n-1)*(n-2)*(n-3)*(n-4)*(n-5) =\\ -(n-1)!/(n-6)!\\\\" align="absmiddle" class="latex-formula">
0\\\\ (n-1)*(n-2)*(n-3)*(n-4)*(n-5) =\\ (-m-1)*(-m-2)*(-m-3)*(-m-4)*(-m-5) =\\ (-1)^5(m+1)*(m+2)*(m+3)*(m+4)*(m+5) =\\ -(m+5)!/m!\\\\ " alt="if \ n = 1, 2, 3, 4 \ or \ 5\\\\ 0\\\\ if \ n < 0, \ -n = m, \ m > 0\\\\ (n-1)*(n-2)*(n-3)*(n-4)*(n-5) =\\ (-m-1)*(-m-2)*(-m-3)*(-m-4)*(-m-5) =\\ (-1)^5(m+1)*(m+2)*(m+3)*(m+4)*(m+5) =\\ -(m+5)!/m!\\\\ " align="absmiddle" class="latex-formula">
![(1-n)*(n-2)*(n-3)*(n-4)*(n-5) =\\ -(n-1)*(n-2)*(n-3)*(n-4)*(n-5) =\\ (-1)^6(m+1)*(m+2)*(m+3)*(m+4)*(m+5) =\\ (m+5)!/m!\\\\ (n-1)*(2-n)*(n-3)*(n-4)*(n-5) =\\ (-1)^6(m+1)*(m+2)*(m+3)*(m+4)*(m+5) =\\ (m+5)!/m!\\\\ (1-n)*(2-n)*(3-n)*(4-n)*(5-n) =\\ (-1)^5(n-1)*(n-2)*(n-3)*(n-4)*(n-5)=\\ (-1)^{10}(m+1)*(m+2)*(m+3)*(m+4)*(m+5) =\\ (m+5)!/m! (1-n)*(n-2)*(n-3)*(n-4)*(n-5) =\\ -(n-1)*(n-2)*(n-3)*(n-4)*(n-5) =\\ (-1)^6(m+1)*(m+2)*(m+3)*(m+4)*(m+5) =\\ (m+5)!/m!\\\\ (n-1)*(2-n)*(n-3)*(n-4)*(n-5) =\\ (-1)^6(m+1)*(m+2)*(m+3)*(m+4)*(m+5) =\\ (m+5)!/m!\\\\ (1-n)*(2-n)*(3-n)*(4-n)*(5-n) =\\ (-1)^5(n-1)*(n-2)*(n-3)*(n-4)*(n-5)=\\ (-1)^{10}(m+1)*(m+2)*(m+3)*(m+4)*(m+5) =\\ (m+5)!/m!](https://tex.z-dn.net/?f=%281-n%29%2A%28n-2%29%2A%28n-3%29%2A%28n-4%29%2A%28n-5%29+%3D%5C%5C+-%28n-1%29%2A%28n-2%29%2A%28n-3%29%2A%28n-4%29%2A%28n-5%29+%3D%5C%5C+%28-1%29%5E6%28m%2B1%29%2A%28m%2B2%29%2A%28m%2B3%29%2A%28m%2B4%29%2A%28m%2B5%29+%3D%5C%5C+%28m%2B5%29%21%2Fm%21%5C%5C%5C%5C+%28n-1%29%2A%282-n%29%2A%28n-3%29%2A%28n-4%29%2A%28n-5%29+%3D%5C%5C+%28-1%29%5E6%28m%2B1%29%2A%28m%2B2%29%2A%28m%2B3%29%2A%28m%2B4%29%2A%28m%2B5%29+%3D%5C%5C+%28m%2B5%29%21%2Fm%21%5C%5C%5C%5C+%281-n%29%2A%282-n%29%2A%283-n%29%2A%284-n%29%2A%285-n%29+%3D%5C%5C+%28-1%29%5E5%28n-1%29%2A%28n-2%29%2A%28n-3%29%2A%28n-4%29%2A%28n-5%29%3D%5C%5C+%28-1%29%5E%7B10%7D%28m%2B1%29%2A%28m%2B2%29%2A%28m%2B3%29%2A%28m%2B4%29%2A%28m%2B5%29+%3D%5C%5C+%28m%2B5%29%21%2Fm%21+)
![2) \ (n-1)*(n-2)*(n-3)*(n-4)*(n-5)=\\ (n^2-3n+2)(n^2-7n+12)(n-5) =\\ (n^2-3n+2)(n^3-12 n^2+47 n-60) =\\ n^5 - 12n^4 +47n^3-60n^2-3n^4+36n^3-141n^2+\\180n+2n^3-24n^2+94n-120 =\\ n^5 - 15n^4 + 85n^3 - 225n^2 + 274n - 120\\\\ (1-n)*(n-2)*(n-3)*(n-4)*(n-5) =\\ -(n-1)*(n-2)*(n-3)*(n-4)*(n-5) =\\-n^5+15n^4 - 85n^3 + 225n^2 - 274n +120\\\\ 2) \ (n-1)*(n-2)*(n-3)*(n-4)*(n-5)=\\ (n^2-3n+2)(n^2-7n+12)(n-5) =\\ (n^2-3n+2)(n^3-12 n^2+47 n-60) =\\ n^5 - 12n^4 +47n^3-60n^2-3n^4+36n^3-141n^2+\\180n+2n^3-24n^2+94n-120 =\\ n^5 - 15n^4 + 85n^3 - 225n^2 + 274n - 120\\\\ (1-n)*(n-2)*(n-3)*(n-4)*(n-5) =\\ -(n-1)*(n-2)*(n-3)*(n-4)*(n-5) =\\-n^5+15n^4 - 85n^3 + 225n^2 - 274n +120\\\\](https://tex.z-dn.net/?f=2%29+%5C+%28n-1%29%2A%28n-2%29%2A%28n-3%29%2A%28n-4%29%2A%28n-5%29%3D%5C%5C+%28n%5E2-3n%2B2%29%28n%5E2-7n%2B12%29%28n-5%29+%3D%5C%5C+%28n%5E2-3n%2B2%29%28n%5E3-12+n%5E2%2B47+n-60%29+%3D%5C%5C+n%5E5+-+12n%5E4+%2B47n%5E3-60n%5E2-3n%5E4%2B36n%5E3-141n%5E2%2B%5C%5C180n%2B2n%5E3-24n%5E2%2B94n-120+%3D%5C%5C+n%5E5+-+15n%5E4+%2B+85n%5E3+-+225n%5E2+%2B+274n+-+120%5C%5C%5C%5C+%281-n%29%2A%28n-2%29%2A%28n-3%29%2A%28n-4%29%2A%28n-5%29+%3D%5C%5C+-%28n-1%29%2A%28n-2%29%2A%28n-3%29%2A%28n-4%29%2A%28n-5%29+%3D%5C%5C-n%5E5%2B15n%5E4+-+85n%5E3+%2B+225n%5E2+-+274n+%2B120%5C%5C%5C%5C)
![(1-n)*(2-n)*(n-3)*(n-4)*(n-5) =\\ -(n-1)*(n-2)*(n-3)*(n-4)*(n-5) =\\-n^5+15n^4 - 85n^3 + 225n^2 - 274n +120\\\\ (1-n)*(2-n)*(3-n)*(4-n)*(5-n) =\\ (-1)^5(n-1)*(n-2)*(n-3)*(n-4)*(n-5) =\\-(n-1)*(n-2)*(n-3)*(n-4)*(n-5) =\\-n^5+15n^4 - 85n^3 + 225n^2 - 274n +120 (1-n)*(2-n)*(n-3)*(n-4)*(n-5) =\\ -(n-1)*(n-2)*(n-3)*(n-4)*(n-5) =\\-n^5+15n^4 - 85n^3 + 225n^2 - 274n +120\\\\ (1-n)*(2-n)*(3-n)*(4-n)*(5-n) =\\ (-1)^5(n-1)*(n-2)*(n-3)*(n-4)*(n-5) =\\-(n-1)*(n-2)*(n-3)*(n-4)*(n-5) =\\-n^5+15n^4 - 85n^3 + 225n^2 - 274n +120](https://tex.z-dn.net/?f=%281-n%29%2A%282-n%29%2A%28n-3%29%2A%28n-4%29%2A%28n-5%29+%3D%5C%5C+-%28n-1%29%2A%28n-2%29%2A%28n-3%29%2A%28n-4%29%2A%28n-5%29+%3D%5C%5C-n%5E5%2B15n%5E4+-+85n%5E3+%2B+225n%5E2+-+274n+%2B120%5C%5C%5C%5C+%281-n%29%2A%282-n%29%2A%283-n%29%2A%284-n%29%2A%285-n%29+%3D%5C%5C+%28-1%29%5E5%28n-1%29%2A%28n-2%29%2A%28n-3%29%2A%28n-4%29%2A%28n-5%29+%3D%5C%5C-%28n-1%29%2A%28n-2%29%2A%28n-3%29%2A%28n-4%29%2A%28n-5%29+%3D%5C%5C-n%5E5%2B15n%5E4+-+85n%5E3+%2B+225n%5E2+-+274n+%2B120+)